Analysis of Madden-Julian Oscillation (MJO) on extreme rainfall event in the west coastal south Sulawesi for mitigation disaster - Rekun Matandung; Eko Hadi Sujiono; Subaer Subaer (Universitas Andalas, 2023)
Madden Julian Oscillation (MJO) is one of the global phenomena that affects weather and climate conditions in Indonesia. MJO increases the rainfall rate and causes a plethora of extreme rainfall occurrences in areas along its trajectory. Those extreme rainfall events could trigger hydrometeorological hazards that endanger the surrounding environment. As the first step to analyse this extreme weather event, this research tries to determine the threshold of the extreme rainfall rate. The method used for determining the threshold is the statistical method 98th percentile. The next step is to identify the frequency trend of the extreme rainfall in the period of 1991 to 2020, by measuring the rainfall rate and comparing it with the normal value. If the rainfall rate is above the normal condition inÂ a certain threshold, then it is considered an extreme rainfall event. After that, these extreme rainfall occurrences are compared to the active MJO phase to find out the influence of MJO to the rainfall in the west coast of South Sulawesi. Then, the dynamical atmospheric conditions are to be analysed during those extreme rainfall events. The result shows that the frequency trend of extreme rainfall events are generally negative in 5 (five) regions, which means an insignificant correlation between MJO andÂ rainfall rate. In contrast, 3 (three) other regions show a positive trend. The influence of an active MJO on the extreme rainfall rate is about 34,1%. Meanwhile, the rest for about 65,9% is influenced by other factors. The use of MJO indices for generating early warning hydrometeorological disasters is by utilising the MJO monitoring data, supported with the analysis of dynamical atmospheric condition in the west coast of South Sulawesi.